Anticoagulation in patients with atrial fibrillation and heart failure: Insights from the NCDR PINNACLE‐AF registry. Issue 3 (30th January 2019) - Contreras, Johanna P.; Hong, Kimberly N.; Castillo, Javier; Marzec, Lucas N.; Hsu, Jonathan C.; Cannon, Christopher P.; Yang, Song; Maddox, Thomas M.
Abstract : Background: In non‐valvular atrial fibrillation (NVAF) patients, congestive heart failure (CHF) confers an increased risk of stroke or systemic thromboembolism. This risk is present in both heart failure (HF) with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF). It is unclear if clinicians account for both types of CHF in their NVAF anticoagulation practices. Accordingly, we characterized current outpatient anticoagulation trends in NVAF patients with HFpEF compared to patients with HFrEF. Methods: The outpatient NCDR PINNACLE‐AF registry was analyzed to identify patients with NVAF and CHF. The study population was subdivided into HFpEF (ie, LVEF ≥ 40%) and HFrEF (LVEF < 40%). Anticoagulation rates by CHF group were compared and stratified by CHA2 DS2 ‐VASc score. Results: A total of 340 127 patients with NVAF and CHF were identified, of whom 248 136 (73.0%) were classified as HFpEF and 91 991 (27.0%) as HFrEF. Patients with HFpEF had higher mean CHA2 DS2 ‐VASc scores and were more likely to be female, older, and have hypertension ( P < 0.001). Unadjusted anticoagulation rates were significantly lower in patients with HFpEF compared to those with HFrEF (60.6% vs 64.2%, respectively). Lower rates of anticoagulation in the HFpEF group persisted after risk adjustment (RR: 0.93 [95% CI: 0.91, 0.94]). Stratification by CHA2 DS2 ‐VASc score demonstrated that lower rates of anticoagulation in patients with HFpEF persisted until a score of ≥5. Conclusions: Patients with NVAF and HFpEF have significantly lower anticoagulation rates when compared to their HFrEF counterparts. These findings suggest a potential underappreciation of HFpEF as a risk factor in patients with NVAF.